Framing the shot: tracing the dialectical development of sports discourse in India through advertising images. Issue 5 (20th October 2022) - Jha, Sonal
Abstract : This paper defines the category of the sports image ad in contradistinction to the sports narrative ad. Image ads, unlike narrative ads, are characterised by the use of sports images without employing spatio-temporal logic and sequentiality. After engaging in a brief discussion of the term image, the paper focuses on a structuralist study of the images employed in sports image ads on Indian television, and subjects them to rigorous semantic and syntactic analysis, using numerous examples, in order to extract the implications these images have for Indian sports discourse. It also undertakes a historical analysis of the changes that sports images have undergone over time in order to trace the changes in sports discourse in India since the advent of television in the 1980s.